Pengaruh Marketing Mix Terhadap Minat Anggota Memilih Pembiayaan Murobahah di KJKS Kopermas Kecamatan Sawahan Kabupaten Madiun: Pengaruh Marketing Mix Terhadap Minat Anggota Memilih Pembiayaan Murobahah di KJKS Kopermas Kecamatan Sawahan Kabupaten Madiun - novy rachma (Universitas Merdeka Madiun, 2022)
Murobahah financing is one of the superior programs offered in the KJKS Kopermas Sawahan Madiun to help the community's economy. In marketing of Murobahah financing product, KJKS Kopermas Sawahan Madiun applies a marketing mix strategy, especially to increase the interest of members in choosing the financing product. This study aims to determine the effect of partially and simultaneously the marketing mix which includes product, price, place, promotion, people, physical evidence and process on the interest of members in choosing Murobahah financing at KJKS Kopermas Sawahan Madiun. The population in this study were all members of the Murobahah financing at KJKS Kopermas Sawahan Madiun from January 2020 to August 2021, totaling 224 people. The sample were 25% of the population, amounting to 56 people. Sampling using proportional random sampling technique. The research instrument used a questionnaire. The data analysis technique used the classical assumption test, multiple linear regression analysis, the coefficient of determination analysis, and hypothesis testing using the t test and F test. The results of the study are: 1) Marketing mix (product, price, place, promotion, people, physical evidence, process ) partially affects the interest of members in choosing Murobahah financing at KJKS Kopermas Sawahan Madiun, 2) Marketing mix (product, price, place, promotion, people, physical evidence, process) simultaneously affects the interest of members in choosing Murobahah financing at KJKS Kopermas Sawahan Madiun Murobahah financing is one of the superior programs offered in the KJKS Kopermas Sawahan Madiun to help the community's economy. In marketing of Murobahah financing product, KJKS Kopermas Sawahan Madiun applies a marketing mix strategy, especially to increase the interest of members in choosing the financing product. This study aims to determine the effect of partially and simultaneously the marketing mix which includes product, price, place, promotion, people, physical evidence and process on the interest of members in choosing Murobahah financing at KJKS Kopermas Sawahan Madiun. The population in this study were all members of the Murobahah financing at KJKS Kopermas Sawahan Madiun from January 2020 to August 2021, totaling 224 people. The sample were 25% of the population, amounting to 56 people. Sampling using proportional random sampling technique. The research instrument used a questionnaire. The data analysis technique used the classical assumption test, multiple linear regression analysis, the coefficient of determination analysis, and hypothesis testing using the t test and F test. The results of the study are: 1) Marketing mix (product, price, place, promotion, people, physical evidence, process ) partially affects the interest of members in choosing Murobahah financing at KJKS Kopermas Sawahan Madiun, 2) Marketing mix (product, price, place, promotion, people, physical evidence, process) simultaneously affects the interest of members in choosing Murobahah financing at KJKS Kopermas Sawahan Madiun